Studi Komparasi Metode Pembelajaran Kooperatif STAD dan Ekspositori dalam Meningkatkan Learning Outcome pada Computer for Communication - Waris, Abdul; Rochman, Fatkhur (Jurnal Pendidikan Ekonomi Undiksha, 2021)
The problem often experienced in learning computer for communication to achieve maximum learning outcomes is the accuracy in presenting the materials, so the method used matches the characteristics of the learning material. In this case, the selection of teaching methods must be adjusted to the current situation and condition to obtain innovative and effective method because the students’ ability is heterogeneous. This study aims to determine students’ learning outcomes using cooperative learning STAD, to determine students’ learning outcomes using expository, as well as to find out the difference students’ learning outcomes between cooperative learning STAD and expository methods. Therefore, this study was designed using quasy-experimental with pre-test and post-test non-equivalent control group design. The population was students of D3 Business Administration Program of Politeknik Negeri Malang consisting of two groups, control and experimental class as a sample. Quantitative statistical analysis was used as a tool in this study. Through t-test, it is found the results of obtained t-count is 3.803 and higher than t table = 1.99. It means that there was a significant difference between the learning outcome of the control and the experimental group on computer for communication subject.